TONG NGIN FAN NGIN JIT JONG: LOCAL RELIGIOUS LITERATURE AS A GRASSROOTS MODEL FOR RELIGIOUS MODERATION POLICY IN SOUTHEAST ASIA - Jati Marta, Dwi (The Ministry of Religious Affairs, The Republic of Indonesia, 2025)
This study examines the local expression Tong Ngin Fan Ngin Jit Jong from Bangka Belitung as a form of local wisdom that functions as a living religious literature, a symbol of tolerance, and a counter to radicalism in Southeast Asia. The research aims to explore how this expression strengthens religious moderation and social resilience in Bangka Belitung. Using a qualitative approach based on literature studies, it analyzes academic sources, historical archives, local media, and policy documents that record the historical development and contemporary meaning of the phrase. The findings reveal that Tong Ngin Fan Ngin Jit Jong, meaning “Chinese and Malay are one,” emerged from a long process of acculturation between Chinese and Malay communities since the 17th century, reinforced through anti-colonial solidarity, and institutionalized within regional cultural policies. This expression is not merely a slogan but a living cultural-religious text embodying values of equality, interfaith brotherhood, and mutual cooperation. Another key finding highlights the role of local media in reproducing narratives of harmony and the expression’s contribution to strengthening social resilience amid rising intolerance and polarization. Conceptually, this study contributes to religious literature studies by positioning Tong Ngin Fan Ngin Jit Jong as a model of grassroots pluralism relevant to other multicultural contexts in Southeast Asia. The study’s limitation lies in the absence of ethnographic field data; thus, future research is recommended to explore the lived experiences of younger generations through participatory approaches.